Strategi Komunikasi Binluh Penyuluh Agama Hindu Kementerian Agama Kota Denpasar dalam Meningkatkan Sraddha dan Bhakti Masyarakat Hindu di Kota Denpasar - Ratih, Ida Ayu; Relin D.E; I Nyoman Ananda (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Before the Covid-19 pandemic, Hindu extension workers conducted face-to-face coaching for the community. However, after the Covid-19 pandemic, community formation has been disrupted due to regulations from the government that prohibit gathering with large numbers of people. In the midst of changes in communication media in this new normal era, of course, there are difficulties in implementing counseling through video. Is there a significant difference in the increase of Hindu Sraddha and Bhakti if guidance and counseling (Binluh) are carried out through videos shared through social media. Therefore, researchers are interested in further studying the phenomenon so that it is poured in a scientific paper entitled